2006
DOI: 10.1016/j.juro.2006.04.076
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Perioperative Plan for Radical Cystectomy and Urinary Intestinal Diversion: Effects, Limits and Complications of Early Artificial Nutrition

Abstract: Early postoperative artificial nutrition did not affect the return of bowel function or postoperative protein depletion. Different strategies for more effective nutritional support will be explored in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
0
23
0
2
Order By: Relevance
“…A recent prospective analysis of 28 RC patients demonstrated that the use of a combination protocol of TPN and enteral nutrition was not effective at reducing post-operative ileus and did not prevent the decline of serum chemistry markers such as serum albumin 28. However, this study’s power to detect a difference in complication rates or surrogate markers may be limited because the researchers did not target an at-risk population and because of the small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…A recent prospective analysis of 28 RC patients demonstrated that the use of a combination protocol of TPN and enteral nutrition was not effective at reducing post-operative ileus and did not prevent the decline of serum chemistry markers such as serum albumin 28. However, this study’s power to detect a difference in complication rates or surrogate markers may be limited because the researchers did not target an at-risk population and because of the small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…Maffezzini et al. devised a novel peri‐operative pathway in RC, with similar principles to those of an ERAS protocol . Patients had bladder reconstruction using intestinal segments (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The main study aim was to minimize the impact of major urological ablative and reconstructive surgery in an elderly population, with significant comorbidities . Clinical outcomes focused on postoperative bowel function and protein depletion . The initial trials demonstrated a quicker return to normal bowel function.…”
Section: Methodsmentioning
confidence: 99%
“…In patients undergoing RC with urinary diversion, the early NGT removal seems to influence positively the recovery of bowel function (Donat et al, 1999;Inman et al, 2003;Pruthi et al, 2003;Maffezzini et al, 2006Maffezzini et al, , 2007Maffezzini et al, , 2008De Vries et al, 2012;.…”
Section: Bowel Functionmentioning
confidence: 99%
“…Despite these findings, in clinical practice, there is still a wide range of opinions regarding post‐RC nutrition management. Moreover, some research studies provide contrasting results and findings one from another (Thurairaja et al ., ; Barrass et al ., ; Maffezzini et al ., ; Mathur et al ., ; Daneshmand et al ., ; Karl et al ., ; Baack Kukreja et al ., ; Declercq et al ., ).…”
Section: Introductionmentioning
confidence: 99%